ChemInform Abstract: Synthesis and Biological Evaluation of Novel Benzimidazole Derivatives Bearing a Heterocyclic Ring at 4/5 Position. Issue 51 (17th December 2013) - Wubulikasimu, Reyila; Yang, Yanbing; Xue, Fei; Luo, Xianjin; Shao, Dongping; Li, Yuhuan; Gao, Rongmei; Ye, Weidong
Abstract The synthesis of a range of benzimidazole derivatives bearing heterocyclic rings is described by the employment of benzimidazole‐4/5‐carboxylic acid derivatives as substrates.